NGC 2571: An intermediate-age open cluster with a White Dwarf candidate - Giorgi, Edgard Ervar Salvador (2002)
CCD UBVI imaging photometry was carried out in the field of the open cluster NGC 2571. From the analysis of our data we state the cluster is at a distance of 1380 ± 130 pc and its age is 504±10 ×106 yr. The cluster mass function has a slope larger than a typical Salpeter's law. There are two notorious features in NGC 2571: the cluster contains a high proportion of stars located below the reference line that are serious candidates to be metallic line stars (probably Am-Fm), and shows also a sharp gap along its main sequence that cannot be explained by a random process nor by a biased rejection of cluster members. A striking blue object was detected in the cluster field that could be a white dwarf candidate.